Pricing strategy for video migration based on truthful auction mechanism - ONGXin C; ILing-ling Z; UNJin-guang S (Tongxin xuebao)
In order to decrease the unit costs of video service, pricing strategy LBAS for video migration based on truthful auction mechanism was proposed. Firstly, according to the principles of market economy prices, service prices using the future video demand as independent variable were laid down by the VoD provider, so as to decrease the costs of the VoD provider. Secondly, a distance function was designed to measure the unit costs of video service. The proposed function computes the distance between the costs providing by cloud providers and expected prices offering by the VoD provider, and the obtained distance was used to determine who can win the auction. Thirdly, replaceable video alloca-tion algorithm based on the benefits of cloud providers was presented. The proposed algorithm increases the satisfaction of cloud providers and decreases the costs of the VoD provider. Finally, the AEM algorithm was improved through estab-lishing the detection mechanism of video number, so as to adapt to the low-bid auction. The improved algorithm avoids the collusion among bidders and assurances the benefits of the VoD provider. The experiment results demonstrate that LBAS can decrease 10% of the costs compared to the VMC strategy.